2009
DOI: 10.1016/j.ecolind.2008.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Feeding diversity in macroinvertebrate communities: A contribution to estimate the ecological status in shallow waters

Abstract: The feeding diversity of subtidal samples of macroinvertebrates from Ria Formosa was estimated with Shannon Wiener information index and complementary evenness. The results were compared with other commonly used methodologies under the European water framework directive, such as diversity indices, AMBI and ITI.Assuming that in a healthy environment all feeding groups are present, and that no group clearly dominates, the feeding diversity is expected to be maximal and the evenness feeding diversity will be clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 43 publications
0
29
0
1
Order By: Relevance
“…Many works demonstrate that benthic macroinvertebrates community can also be altered in response to anthropogenic environmental changes, as land uses (Miserendino et al 2011), riparian forest impacts and effluents loading (Baptista et al 2007, Couceiro et al 2007, Gamito & Furtado 2009, Sharma & Rawat 2009 and also by pollution by industrial effluents (Moreno & Callisto 2006). Several taxa from benthic macroinvertebrates community and a wide range of biological indexes and metrics have been widely employed as environmental indicators (Bode et al 2002, Mandaville 2002, Fusari & Fonseca-Gessner 2006, Baptista et al 2007, Baptista 2008, Angradi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many works demonstrate that benthic macroinvertebrates community can also be altered in response to anthropogenic environmental changes, as land uses (Miserendino et al 2011), riparian forest impacts and effluents loading (Baptista et al 2007, Couceiro et al 2007, Gamito & Furtado 2009, Sharma & Rawat 2009 and also by pollution by industrial effluents (Moreno & Callisto 2006). Several taxa from benthic macroinvertebrates community and a wide range of biological indexes and metrics have been widely employed as environmental indicators (Bode et al 2002, Mandaville 2002, Fusari & Fonseca-Gessner 2006, Baptista et al 2007, Baptista 2008, Angradi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In sandy bare bottoms, the opposite occurs; there is a lower number of species but a dominance of suspension-feeders (Gamito, 2008;Gamito and Furtado, 2009). In this habitat, the diversity decreases but the AMBI values also decrease and consequently the reference values for EQS evaluation must be different.…”
Section: Discussionmentioning
confidence: 94%
“…As described in the methodological approach, for significant groups the 95 percentile values were adopted regarding Margalef and ShannonWiener indices; while the AMBI reference values were adjusted to better reflect the expected community composition at shallow coastal lagoons habitats. In general, it was observed that an important proportion of the communities across all habitats at the lagoon was constituted by tolerant species (ecological group EG III) (Figure 4), which are more adapted to the natural environmental fluctuations in the lagoon (Gamito and Furtado, 2009). At muddier sediment habitats (H2 and H4) there was no clear dominance of sensitive species (EG I and EG II) over the remaining groups, and as expected, the presence of opportunistic species (EG IV and V) was of considerable importance; even at seagrass beds (H2) were EG I and II were very well represented.…”
Section: Invertebrate Communities' Structural Distribution Patternsmentioning
confidence: 99%
“…Technol. Dev., 35 (3): 98-109, 2016 some feeding groups might be absent or having low relative abundance and, generally, with one or two groups dominating the community (Gamito and Furtado, 2009).…”
Section: Introductionmentioning
confidence: 99%